Effect of tralokinumab, an interleukin-13 neutralising monoclonal antibody, on eosinophilic airway inflammation in uncontrolled moderate-to-severe asthma (MESOS): a multicentre, double-blind, randomised, placebo-controlled phase 2 trial. Issue 7 (July 2018) - Russell, Richard J; Chachi, Latifa; FitzGerald, J Mark; Backer, Vibeke; Olivenstein, Ronald; Titlestad, Ingrid L; Ulrik, Charlotte Suppli; Harrison, Timothy; Singh, Dave; Chaudhuri, Rekha; Leaker, Brian; McGarvey, Lorcan; et al.
Summary: Background: The role of interleukin 13 in airway inflammation and remodelling in asthma is unclear. Tralokinumab is a human monoclonal antibody that neutralises interleukin 13. We aimed to evaluate whether tralokinumab would have an effect on airway eosinophilic infiltration, blood and sputum eosinophil concentrations, eosinophil activation, and airway remodelling. Methods: We did a multicentre, double-blind, randomised, placebo-controlled phase 2 trial at 15 centres across the UK, Denmark, and Canada. We enrolled participants of either sex aged 18–75 years with inadequately controlled moderate-to-severe asthma for 12 months or more, requiring treatment with inhaled corticosteroids at a stable dose. We randomly assigned participants (1:1) to receive tralokinumab (300 mg) or placebo by an interactive web-based system or voice response system. Participants and study personnel were masked to treatment allocation. Both tralokinumab and placebo were administered subcutaneously every 2 weeks. The primary outcome measure was change from baseline to week 12 in bronchial biopsy eosinophil count. Secondary outcome measures included change in blood and sputum eosinophil counts. Exploratory outcomes included fractional exhaled nitric oxide (FENO) and blood IgE concentrations. Safety analyses were carried out in all participants who received study drug. This trial is registered withClinicalTrials.gov, numberNCT02449473, and with the European Clinical Trials Database, EudraCT 2015-000857-19. Findings: Between Sept 25, 2015, and June 21, 2017, 224 participants were enrolled and screened. Of these participants, 79 were randomly assigned to receive tralokinumab (n=39) or placebo (n=40). Tralokinumab did not significantly affect bronchial eosinophil count compared with placebo at week 12 (treatment effect ratio 1·43, 95% CI 0·63–3·27; p=0·39). Compared with placebo, tralokinumab did not significantly affect blood eosinophil count (treatment effect ratio 1·21, 95% CI 1·00–1·48; p=0·055) or sputum eosinophil count (0·57, 0·06–6·00; p=0·63), but FENO concentration (0·78, 0·63–0·96; p=0·023) and total blood IgE concentration (0·86, 0·77–0·97; p=0·014) were significantly reduced. 33 (85%) of 39 patients receiving tralokinumab and 32 (80%) of 40 receiving placebo reported at least one adverse event during the treatment period. No deaths in either treatment group were observed. Treatment-related adverse events occurred more frequently in the tralokinumab group than in the placebo group (11 [28%] of 39 vs seven [18%] of 40). Interpretation: Tralokinumab did not significantly affect eosinophilic inflammation in bronchial submucosa, blood, or sputum compared with placebo, but did reduce FENO and IgE concentrations. These results suggest interleukin 13 is not crucial for eosinophilic airway inflammation control in moderate-to-severe asthma. Funding: AstraZeneca.